Lifetime posttraumatic stress disorder as a predictor of mortality: a systematic review and meta-analysis - Dinuli Nilaweera; Aung Zaw Zaw Phyo; Achamyeleh Birhanu Teshale; Htet Lin Htun; Jo Wrigglesworth; Caroline Gurvich; Rosanne Freak-Poli; Joanne Ryan (BMC Psychiatry, 2023)
Abstract Background Posttraumatic Stress Disorder (PTSD) could potentially increase the risk of mortality, and there is a need for a meta-analysis to quantify this association. This study aims to determine the extent to which PTSD is a predictor of mortality. Methods EMBASE, MEDLINE, and PsycINFO were searched systematically on 12th February 2020, with updated searches conducted in July 2021, and December 2022 (PROSPERO CRD42019142971). Studies involving community-dwelling participants with a diagnosis of PTSD or PTSD symptoms, and a comparator group of individuals without PTSD, and which assessed mortality risk, were included. A random-effects meta-analysis was conducted on studies reporting Odds Ratio (OR), Hazard Ratio (HR), and Risk Ratio (RR), and subgroup analysis was also performed by age, sex, type of trauma experienced, PTSD diagnosis, and cause of death. Results A total of 30 eligible studies of mostly good methodological quality were identified, with a total of more than 2.1 million participants with PTSD. The majority of studies involved male-dominated, veteran populations. PTSD was associated with a 47% (95% CI: 1.06–2.04) greater risk of mortality across six studies that reported OR/RR, and a 32% increased risk across 18 studies which reported time to death (HR: 1.32, 95% CI: 1.10–1.59). There was very high study heterogeneity (I2 > 94%) and this was not explained by the prespecified subgroup analysis. Conclusion PTSD is associated with increased mortality risk, however further research is required amongst civilians, involving women, and in individuals from underdeveloped countries.